Computational analysis of low velocity impacts on Empty Fruit Bunch (EFB) composite - Zulkepli, I I; Mokhtar, Hanan; Shaik Dawood, M S I; Aminanda, Yulfian; Muhamed Rehan, M S (The Mattingley Publishing Co., Inc., 2020)
This paper is to investigate the impact response on peak force behavior of the material at low velocity impact EFB composite. This is because impact damage on EFB composite is not well-known using quasi-static indentation. Series of quasi-static indentation was conducted in experiment to obtain the impact result. However, more experimental results are required to gain an accurate result. Simulation is useful to predict results at a reduced cost and time. Mesh has been created to simulate EFB composite rectangular panel using LS-Dyna. Material properties of EFB composite obtained from three point bending test experiment using Instron 3367. Mesh density on EFB composite rectangular panel is differed, which are 0.5mm, 1mm, 1.5mm, 2mm, and 2.5 mm, and results from the simulation is compared to the experimental results which show the same pattern as the simulation result. From the study, the result proved that the simulation is in good agreement and has the same trend as the experimental result.